Cemento-Ossifying Fibroma: Clinical, Radiological, and Histopathological Findings - GÜMRÜ TARÇIN, BİRSAY; AKKİTAP, MELDA PELİN; ERDEM, NECİP FAZIL (MARMARA UNIV, INST HEALTH SCIENCES, 2020)
Cemento-ossifying fibroma, which is considered a benign mesenchymal odontogenic tumour of the jaws, is a type of fibro-osseous lesion characterized by slow growth and proliferation of fibrous cellular stroma containing osteoid, bone or cementum-like tissue. The aim of this study was to report a case of cemento-ossifying fibroma in the mandible with clinical, radiological, and histopathological findings and surgical treatment. A 37-year-old woman was admitted to our clinic with the complaint of gradually growing painless swelling in the right mandibular premolar area. Intra-oral examination revealed a bony hard and non-tender mass with intact overlying mucosa on the buccal and lingual aspects of the mandibular right premolar teeth. Periapical, panoramic, and cone beam computed tomography images revealed the presence of a multilocular hypodense lesion with bicortical destruction and expansion in the relevant area. Excisional biopsy of the lesion was performed and histopathological examination exhibited the definite diagnosis of cemento-ossifying fibroma. Clinical, radiological, and histopathological examination should be considered in the diagnosis and treatment planning of cemento-ossifying fibroma.
Keywords: Cemento-ossifying fibroma; fibro-osseous lesion; cone beam computed tomography; TUMORS